Elevating Empowerment: A Holistic Digital Learning Strategy for Women in Aceh Tamiang After the Pandemic - Rita Syntia (AL-ISHLAH: Jurnal Pendidikan, 2023)
Digital learning is an educational strategy that utilises technology to facilitate learning. In the realm of entrepreneurship, proficiency in digital skills is crucial for enhancing sales performance. Women's involvement in entrepreneurship, aiming to bolster the family's financial situation, has a positive influence on enhancing education. A family's economic well-being significantly impacts the educational opportunities available to the children within that family. This study sought to examine the empowerment method required by female-dominated small business players in Aceh Tamiang, both during and after the pandemic. The study used convenience sampling, gathering data through interviews, observations, and documentation. The acquired data underwent analysis through credibility testing, member checks, dependability assessment, conformability evaluation, and transferability examination. The findings indicated that achieving the empowerment of housewives/women as small business participants in Aceh Tamiang necessitates optimal collaboration among the government, private sector, and the community. This empowerment initiative specifically addresses the challenges faced by individuals during the epidemic, including the transition to digital methods of production and marketing.